Vortex-induced forces of crossflow and inline oscillating bluff bodies at moderate Reynolds numbers. (November 2022) - Fan, Dixia; Triantafyllou, Michael S.
Abstract: The Reynolds number (Re) is found to play an important role in the vibration response of a cross-flow (CF) only oscillating cylinder in the uniform flow that the maximum CF displacement ( A y d ) increases with the increase of Re in the sub-critical regime, from 0.6 diameter ( d ) at Re = 1, 000 to 1.1 d at Re = 20, 000. However, no existing research comprehensively studied the Re effect on the rigid cylinder vibrating in both the In-line (IL) and the CF directions. In this paper, with the help of the intelligent towing tank using an adaptive GPR sampling strategy for automatic sequential experimentation, we studied the vortex forces on a rigid cylinder forced to vibrate in the CF-only direction and the combined-IL-and-CF direction. We constructed a functional representation of the hydrodynamic coefficient database for the cylinder forced CF-only vibration (Re from 1200 to 19, 000) and the cylinder combined-IL-and-CF vibration (Re from 1200 to 14, 000). The results reveal that the maximum A y d associated with the zero value of the lift coefficient in phase with velocity C lv = 0 increases significantly with Re for the CF-only vibrating cylinder, which compares well with and explains the trend observed in the free vibration experiment. In the meantime, Re is shown to have a less stronger effect on A y d when the cylinder is allowed to move in both the IL and the CF directions in the sub-critical Re regime. Highlights: Using GPR-driven adaptive sampling strategy, the intelligent towing tank (ITT) constructed comprehensive CF-only and CF-and-IL-combined rigid cylinder forced vibration databases. The comparison of the forced vibration prediction and max amplitude over different Reynolds number of existing free vibration experimental shows a good comparison.